Surgical Excision Of Intraoral Lipoma; Case Report - Nagy, Ahmed Ismail (European Scientific Journal, ESJ, 2016)
Lipoma is a common tumor of soft tissue. Its location on the oral mucosa is rare, representing 1% to 5% of benign oral tumors although it is the most mesenchymal tumor of the trunk and proximal portions of extremities. Lipoma of the oral cavity may occur in any region. The buccal mucosa, tongue, and floor of the mouth are among the common locations. The clinical presentation is typically as an asymptomatic yellowish mass. The overlying epithelium is intact, and superficial blood vessels are usually evident over the tumor. Other benign connective tissue lesions such as granular cell tumor, neurofibroma, traumatic fibroma and salivary gland lesions (mucocele and mixed tumor) might be included in differential diagnosis. We present a case report of oral lipoma in the left side of the lower lip in 18 years old Saudi patient.